2020
DOI: 10.1088/1752-7163/abbf37
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between breath acetone and blood betahydroxybutyrate in individuals with type 1 diabetes

Abstract: Ketone testing is an important element of the self-management of illness in type 1 diabetes. The aim of the present study was to see if a breath test for acetone could be used to predict quantitatively the levels of the ketone betahydroxybutyrate in the blood of those with type 1 diabetes, and thus be used as an alternative to capillary testing for ketones. Simultaneous capillary ketones and breath acetone were measured in 72 individuals with type 1 diabetes attending a diabetes clinic and on 9 individuals adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…There is good agreement between both data sets, and the overall correlation coefficients between breath acetone and blood BOHB are r p = 0.75 (Pearson's, p < 0.05) and r s = 0.74 (Spearman's, p < 0.05). This is in line with previous studies that as well correlated these parameters, for instance, in type‐1 diabetics after overnight fasting ( r p = 0.57 [ 65 ] ), during the day (morning and afternoon, 0.93 [ 66 ] ) or ketoacidosis (0.82 [ 67 ] ) and in healthy subjects during ketogenic diets (0.78 [ 39 ] ) for different concentration ranges. Linear relationships between blood BOHB and breath acetone for the present data (red dashed line, Figure 5), Güntner et al, [ 43 ] (blue dashed line), and the combined data set (green solid line) are indicated together with the equations of those fits and the coefficient of determination ( R 2 = 0.56).…”
Section: Resultssupporting
confidence: 91%
“…There is good agreement between both data sets, and the overall correlation coefficients between breath acetone and blood BOHB are r p = 0.75 (Pearson's, p < 0.05) and r s = 0.74 (Spearman's, p < 0.05). This is in line with previous studies that as well correlated these parameters, for instance, in type‐1 diabetics after overnight fasting ( r p = 0.57 [ 65 ] ), during the day (morning and afternoon, 0.93 [ 66 ] ) or ketoacidosis (0.82 [ 67 ] ) and in healthy subjects during ketogenic diets (0.78 [ 39 ] ) for different concentration ranges. Linear relationships between blood BOHB and breath acetone for the present data (red dashed line, Figure 5), Güntner et al, [ 43 ] (blue dashed line), and the combined data set (green solid line) are indicated together with the equations of those fits and the coefficient of determination ( R 2 = 0.56).…”
Section: Resultssupporting
confidence: 91%
“…Over 100,000 data were collected from 9 different concentrations of acetone balanced with simulated human breath. The data were labeled into several different classes based on the concentration of acetone: background (0 μmol/mol), safe (≤5 μmol/mol), low risk (≤40 μmol/mol), and high risk (>40 μmol/mol). 80% of the data were used for training, 10% were used for testing, and 10% were used for cross-validation.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of acetone in exhaled breath is less than 2 μmol/mol (ppm), and the blood BHB is less than 0.6 mmol/L for nondiabetic ketoacidosis conditions. In diabetic ketoacidosis, the concentration of breath acetone is higher than 40 μmol/mol (ppm), and the blood BHB is higher than 3.0 mmol/L …”
Section: Introductionmentioning
confidence: 99%
“…Patients with diabetes tend to have increased levels of ketone bodies, acetone, acetoacetic acid, and beta-hydroxybutyric acid in blood and urine. Breath acetone has been shown to correlate with the metabolic state in patients with diabetes [ 124 ]. Breath analysis may in the future offer an alternative to blood sampling for glucose monitoring for patients with diabetes mellitus.…”
Section: Factors Affecting Breath Analysismentioning
confidence: 99%